Impact and challenges of enactment for advanced regenerative medicine in South Korea - Kim, Dong-Sook; Bae, SeungJin (Frontiers in Bioengineering and Biotechnology, 2022)
The Korean government has enacted the Act on Advanced Regenerative Medicine and Advanced Biological products (ARMAB) in August 2019, and it has been implemented in 2020. We reviewed the changes made by ARMAB compared to the existing Pharmaceutical Affairs Act and discussed future challenges to accelerate regenerative medicine while ensuring safety and efficacy. This act and regulations focused on the key elements of act as follows: the definition of advanced regenerative medicine (RM), the licensing of related facilities, safety management such as long-term follow-up, clinical research review committee, and establishment of a roadmap. However, how to evaluate post-marketing safety and the details on the criteria of good manufacturing practice (GMP) should be followed. To encourage innovation of RM and protect patient safety, it will be a reference for other countries to benchmark Korea’s enactment of Advanced RM.